(untitled) (World Bulletin of Social Sciences, 2025)
This article examines the development of medical terminology in the Uzbek language, the mechanisms of new word formation, and their role in enriching the national medical lexicon. It analyzes affixation, compounding, semantic, and abbreviated word formation methods, primarily using medical terms as an example. The article also examines the challenges of adapting international medical terms to the Uzbek languag